Probability of Bankruptcy of Coal Mining Firm in Indonesia - Adler Haymans Manurung , Benny Hutahayan , Kevin Deniswara (International Journal of Advanced Science and Technology, 2020)
This research aim to investigate Probability Bankruptcy of Coal Mining Firm in Indonesia. Model Panel Data is used to estimate relationship internal factor and external factor to determine Probability Bankruptcy for period 2016 to 2018. Asset also used as a moderating variable. The results is Debt to Equity Ratio (DER), Gross Profit Margin (GPM), Time Interest Earned (TIE) and Total Asset (TAS) are significant impact to probability bankruptcy. This research also investigated macroeconomic variable to affect Probability Bankruptcy.  Oil Price and Fed Rate are significant affecting probability bankruptcy.  The independent Variables will have significant to affect dependent variable through moderating variable, if the independent variable has significant affecting dependent variable.